Comparison of soil pH measurement in a non tilled vineyard: conventional laboratory values vs. 3100 Veris soil pH sensor readings - Marques da Silva, JR (2013)
This work pretends to compare the soil pH measured by the 3100 Veris sensor with the conventional soil sampling in a specific soil condition of a non tilled vineyard. Whereas high density data was obtained with the soil pH sensor, which were used to delineate a pH surface using a geostatistical algorithm, conventional laboratory values were divided in two sets, depending on their location in a 3 or a 12 years non tilled vineyards. Comparison leads to some differences, but varibility was minor when the area not mobilized for 12 years was considered.